Effectiveness of Xylitol Toothpaste on the Growth and Biofilm Formation of Streptococcus mutans ATCC 25175 - Liyana, Liyana; Ahmad, Iwan; Gunawan, Kirana Lina; Gartika, Meirina (Journal of Syiah Kuala Dentistry Society, 2023)
Background: Several toothpaste ingredients have also been proven to prevent dental caries. An alternative material like xylitol can reduce biofilms and caries formation. Objective: This study aims to test the antibacterial xylitol toothpaste against Streptococcus mutans biofilm. Materials and Methods: The type of this research was true experimental by using two kinds of toothpaste with xylitol active ingredient (samples 1 and 2) and toothpaste with fluoride (sample 3). The toothpaste was diluted using the serial dilution method, and then the minimum inhibitory concentration (MIC), minimum bactericide concentration (MBC), minimum biofilm eradication concentration (MBEC), and minimum biofilm inhibition concentration (MBIC) were examined. The data were analyzed with ANOVA and Pearson correlation with a significance value of p0.005. Results: The MIC values of samples 1, 2, and 3 were 0.39%, 0.78%, and 0.39%, respectively. The MBC of samples 1, 2, and 3 were 12.5%, 25%, and 6.25%, respectively. The results of MBIC samples 1, 2, and 3 were 1.56%, 1.56%, and 0.78%, respectively. The results of MBEC samples 1, 2, and 3 were 6.25%, 6.25%, and 1.56%, respectively. There was a difference in the decrease of the mass of Streptococcus mutans ATCC 25175 biofilm after administration using xylitol and fluoride toothpaste, with a p-value of 0.0295. Additionally, there is a correlation between the time of administration of xylitol toothpaste with the changes in the mass of the biofilm Streptococcus mutans ATCC 25175. Conclusion: Xylitol toothpaste can inhibit the growth and eradication of Streptococcus mutans biofilm ATCC 25175.